Evaluar el sistema de control interno en la E.S.E Hospital La Misericordia de Calarcá en el área de servicio farmacéutico (2011)
Implementation of Internal Control Standard Model of State MECI 1000: 2005, Generally Accepted Auditing Standards N.A.G.A and the Law 87 of 1993 as a main rule which requires all state entities to have internal control. Internal control aims to protect the resources of an organization, ensuring the proper administration of the same, thus ensuring efficiency, effectiveness and safety for the company. So we need an evaluation to the System Control Service Area of pharmacist from the Hospital La Misericordia Township of Calarcá, relying on the rule governing state entities in the control.